Digital Transformation in Global Education: Challenges and Opportunities in the 21st Century - Flynn Archer; Hudson Vale Sterling (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The 21st century has witnessed a rapid digital transformation in global education, reshaping traditional learning paradigms and creating new opportunities and challenges. This study explores the impact of digitalization on educational accessibility, teaching methodologies, and student engagement. The research employs a qualitative approach, analyzing current trends, technological advancements, and policy implementations in various educational systems. The findings highlight the benefits of digital transformation, such as increased accessibility, personalized learning experiences, and the integration of artificial intelligence in education. However, challenges such as the digital divide, cybersecurity concerns, and the need for teacher training persist. The study underscores the importance of strategic policies and investment in digital infrastructure to ensure equitable and effective educational transformation worldwide.